2003
DOI: 10.3171/jns.2003.98.3.0477
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-based assessment of the severity of a concussion

Abstract: This paper represents the first documentation of empirically derived indicators of the clinical course of postconcussion symptom resolution. Self-reported memory problems apparent 24 hours postconcussion were robust indicators of the severity of sports-related concussion and should be a primary consideration in determining an athlete's readiness to return to competition. A decline on neurocognitive testing was the only objective measure significantly related to the duration of symptoms. Neither a brief LOC nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 22 publications
7
133
0
Order By: Relevance
“…29 Football players are among the team sport athletes at highest risk for catastrophic cervical spine injuries. 71 The annual incidence of catastrophic cervical spine injuries appears higher for collegiate players than for high school players (4.72 vs 1.10 per 100 000 participants). 77 68 Other authors have also cautioned that a lack of proper training may increase risk of injury.…”
Section: Injuries Associated With Tacklingmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Football players are among the team sport athletes at highest risk for catastrophic cervical spine injuries. 71 The annual incidence of catastrophic cervical spine injuries appears higher for collegiate players than for high school players (4.72 vs 1.10 per 100 000 participants). 77 68 Other authors have also cautioned that a lack of proper training may increase risk of injury.…”
Section: Injuries Associated With Tacklingmentioning
confidence: 99%
“…17,18,71,72,79 A recent initiative by USA Football emphasizes keeping the head up during tackling to prevent catastrophic injuries as well as concussions, although this new coaching method needs further study.…”
Section: Other Strategies For Reducing Injuries Teaching Proper Tacklmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrograde amnesia occurs when the athlete does not remember events that occurred before the injury. Some authors consider postconcussion memory problems to be strongly associated with concussion severity, so memory deficits are often a major consideration in determining fitness to return to play after injury [26,31]. However, some studies consider the nature and duration of other postconcussion symptoms, such as headaches, dizziness, and blurred vision, to be more important predictors of injury severity than memory deficits alone [32][33].…”
Section: Grading Scales and Return To Playmentioning
confidence: 99%
“…The duration of LOC is a relatively good predictor of outcome in severe TBI but a less reliable predictor in MTBI [26][27]. Lovell et al studied 383 patients with MTBI and found that those with LOC did not necessarily have greater neuropsychological impairment [28].…”
Section: Grading Scales and Return To Playmentioning
confidence: 99%